(untitled) (Journal of Forestry, 2025)
There are still unexplored connections between tree growth and remotely sensed time-series are waiting to be discovered. Research results that combine dendrochronological data (tree-ring widths) and remotely sensed image time-series are generally scarce. We provide new findings that relate to the radial growth of different tree species (pedunculate and Turkey oak, European beech and Scots pine) and MODIS Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI) and Land Surface Temperatures (LST) daytime and night-time time-series. Significant correlations between MODIS observations (from 2000 to 2013, averaged to monthly and annual values) and radial growth of the trees have been found. All four tree species were statistically related to each of the four indices for some specific months within the growing season. LSTd annual values were significantly related to the radial growth of three species (Turkey oak, beech and pine) and annual EVI and LSTn to a single species (pine and beech, respectively). NDVI did not statistically correlate (p<0.05) with any of the tree-ring width chronologies. Values of EVI were statistically negatively related to Scots pine growth patterns (coefficient -0.546). LSTd was statistically related to the growth of Turkey oak (coefficient -0.571), European beech (coefficient -0.538) and Scots pine (coefficient -0.569), while LSTn had a high negative correlation with European beech (coefficient -0.674).